(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The study was conducted to determine the efficacy of Tulsi (Ocimum sanctum ) leaves extract as a growth promoter in broiler. Thirty (30) day-old broiler chicks were purchased from Kazi hatchery and after seven days of acclimatization in the poultry shed of Pharmacology department randomly divided into two groups I0 and I1. No vaccination schedule was practiced and no antibiotics were added in rations. Group was supplemented with Tulsi (Ocimum sanctum) leaves extract @ 2ml/litre in drinking water. Weekly observations were recorded for live body weight gain upto 5th weeks and blood test was performed at 17th and 35th days age of broiler to observe the hematological changes between control (Group) and treatment (Group) group. The treatment group (Group A) recorded statistically non- significant for live body weight at 1st and 2nd weeks than that of control group (Group B) but found statistically significant at 3rd (p<0.01), 4th (P<0.05) and 5th (P<0.01) weeks of age and the Hematological parameters (TEC, PCV, Hb and ESR) showed statistically significant (p<0.01) difference as compared to control group. Res. Agric., Livest. Fish.2(1): 97-102, April 2015